Learning in double time: The effect of lecture video speed on immediate and delayed comprehension - Murphy, Dillon H.; Hoover, Kara M.; Agadzhanyan, Karina; Kuehn, Jesse C.; Castel, Alan D. (Applied cognitive psychology, 2022)
We presented participants with lecture videos at different speeds and tested immediate and delayed (1 week) comprehension. Results revealed minimal costs incurred by increasing video speed from 1x to 1.5x, or 2x speed, but performance declined beyond 2x speed. We also compared learning outcomes after watching videos once at 1x or twice at 2x speed. There was not an advantage to watching twice at 2x speed but if participants watched the video again at 2x speed immediately before the test, compared with watching once at 1x a week before the test, comprehension improved. Thus, increasing the speed of videos (up to 2x) may be an efficient strategy, especially if students use the time saved for additional studying or rewatching the videos, but learners should do this additional studying shortly before an exam. However, these trends may differ for videos with different speech rates, complexity or difficulty, and audiovisual overlap.